Postchemotherapy Residual Tumor Resection in Patients with Elevated Tumor Markers. Issue 3 (25th March 2022) - Che, Yue; Buddensieck, Carolin; Albers, Peter; Lusch, Achim; Winter, Christian; Siemer, Robert große; Hiester, Andreas
Abstract : Purpose: The oncologic benefit of postchemotherapy (PC) residual tumor resection (RTR) in patients with germ cell tumors and elevated serum tumor markers (STMs) remains unclear. This analysis was performed to better define patients who benefit from surgery in this setting. Materials and Methods: Of 575 PC-RTR procedures (July 2008–July 2019) 153 were performed in patients with elevated STMs (human chorionic gonadotropin [HCG] >2.0 mIU/ml, alpha-fetoprotein [AFP] >7.0 µg/l), including 55 after first line and 98 after second or later line chemotherapy. Results: Viable cancer in the resected specimen was significantly more common in the salvage group than in the first line group (48.98% vs 16.36%, p=0.0001988) and was a predictor of survival in both groups. A preoperative serum level of AFP ≥30 µg/l was a significant predictor of viable cancer in the first line and salvage groups (55.56% [p=0.0157] and 66.67% [p=0.0017], respectively). The overall relapse-free survival rate (22.7% and 50%, p=0.00032) and overall survival rate (37.8% and 65%, p=0.0059) were significantly worse in the salvage group than in the first line group. A preoperative serum level of AFP ≥30 µg/l and viable cancer/teratoma found in the histological examination of the RTR specimens were significant predictors of relapse after first line chemotherapy. Serum AFP ≥30 µg/l and HCG ≥20 mIU/ml were significant factors affecting survival in the first line group. Conclusions: Patients with AFP serum levels >30 µg/l and HCG ≥20 mIU/ml after first line chemotherapy should receive salvage chemotherapy instead of surgery. After second or later line therapy, the prognosis of patients with elevated markers and surgery is poor regardless of the tumor marker levels. However, 38% of these patients are long-term survivors, which justifies PC-RTR in this setting.